Analysis of vicuña fibre production in semi-captivity and in the wild in Apurímac, Peru - Valenzuela Pinares, Miguel Angel (2020)
The aim of this study was to analyse the production of vicuña (Vicugna mensalis mensalis) fibre in semi-captivity and in the wild between 2008 and 2016 in the Apurímac region of Peru, as well as to determine the population of vicuñas captured and sheared and the effect of sex, age and management system in the fibre production. The production of vicuña fibre in the nine years of the study was 2 623 kg, annual average of 295.7 kg, yield of 152.76 g/vicuña and a range of variation of 54-426 g. Fibre production had an annual growth rate of 9.45% and a capture rate of 10.34%. Factorial analysis showed a significant difference (p<0.05) for the interactions of years, age, sex and simple effects.